Study of Coastal Community Behavior Impacts on the Community Economy (Case Study in Jangkar Village, Jangkar District, Situbondo District) - Safrieta Jatu Permatasari; Dimas Imaniar (Journal of Aquaculture Science, 2021)
The coastal area of Jangkar Village, Jangkar District is a transitional area between sea and land. The development of the coastal area of Jangkar Village often comes under pressure from various human activities and phenomena that occur on land and sea. This is illustrated in Jangkar Village, Jangkar District. Jangkar Village has a unique geographic location compared to other beaches, especially with the presence of a port that connects the waterway to Madura Island and fish auction sites, as well as cheap culinary stalls that attract tourists to visit. The economic condition of the people in Jangkar Village is currently experiencing almost no change due to the behavior of the people who only depend on sea products for their livelihoods. The purpose of this research is to examine the behavior of coastal communities that has an impact on the social and economic aspects of the community. This research uses a qualitative descriptive method that is carried out with a sociological approach, or in public administration research it is commonly called applied normative / empirical normative. The sample selection was carried out by purposive sampling with government informants and fishermen groups. The results showed that the behavior of coastal communities has an effect on economic conditions. This is also influenced by the low level of community education about the coastal area of Jangkar Village. The government should be able to work together with the community to improve the quality of education in the fishing village of Jangkar Village so that it has a positive impact on the economy of the people in the Jangkar village area.Keyword : Community Economy, Coastal Society, Behavior.